In Tech We Trust? On Salvation through Technology. - Menacho, Joaquin; Puig-Puig, Llorenç (Zygon: Journal of Religion & Science, 2025)
With its accelerated progress, technology has become the main source of hope for humanity, and so-called human enhancement technologies are the exponent of this trend. Technological progress has not just put forward therapeutic applications but proposes significant enhancements in human beings. And there is an implicit desire for technology to lead us to a kind of quasi-immortality. Transhumanism is the most explicit expression of this trend. This article contrasts Christian hope in God's redemption with the hope offered by transhumanism. The differences are articulated around three axes: the desire for immortality as the driving force of a relentless search; the contrast between a salvation that is conquered and one that is received; and the collective dimension of salvation as opposed to the transhumanist program, which, while aiming to bring its benefits to the entire population, maintains an individual salvation project. This work highlights certain reference points that can guide reflection on the challenges technoscience poses.